2011
DOI: 10.1007/s00213-011-2419-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic atomoxetine treatment during adolescence decreases impulsive choice, but not impulsive action, in adult rats and alters markers of synaptic plasticity in the orbitofrontal cortex

Abstract: These data suggest that repeated administration of atomoxetine in adolescence can lead to stable decreases in impulsive choice during adulthood, potentially via modulating development of the orbitofrontal cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 118 publications
(134 reference statements)
8
50
0
Order By: Relevance
“…Impulsive choice (cognitive impulsivity) involves various risk and decision-making behaviours, which are shown to be mediated by dissociable brain substrates and neurotransmitter system [68,69]. In accordance with our study, experiments on animals [42,43] and humans [44][45][46] have indicated that BDNF levels are affected by conditions that are described by disruptions in the control of impulses.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Impulsive choice (cognitive impulsivity) involves various risk and decision-making behaviours, which are shown to be mediated by dissociable brain substrates and neurotransmitter system [68,69]. In accordance with our study, experiments on animals [42,43] and humans [44][45][46] have indicated that BDNF levels are affected by conditions that are described by disruptions in the control of impulses.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, higher BDNF production has also been associated with various forms of impulse control disorders, such as severe gambling disorder [37], attention deficit hyperactivity disorder [38], personality disorders with high impulsiveness [39,40], and novel psychoactive substance use [41]. Experiments on animals [42,43] as well on humans [44][45][46] have indicated that BDNF levels are affected by conditions that are described by disruptions in the control of impulses. However, little is known to date about neurobiological factors associated with more specific manifestation of impulsivity, for example, risk-taking or factors that may predispose drug users to increased risk-taking behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, children with ADHD who are considered to be more impulsive showed either an increase in impulsive action or impulsive choice, but behavior on the two types of tasks was not correlated (Sonuga-Barke, 2002). In addition, a recent study found that adolescent atomoxetine treatment decreases impulsive choice without affecting impulsive action in adulthood (Sun et al, 2012). Therefore, exposure to high levels of stress hormones during adolescence may manifest as differential risk for certain psychiatric diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Once stable baseline behavior had been established, drugs were administered in the following order: amphetamine (0, 0.3, 0.6, 1.0 mg/kg; Sun et al, 2012), ethanol (0, 0.3, 0.6, 1.0 g/kg; Bizarro et al, 2003), and caffeine (0, 5, 10, 20 mg/kg; Bizarro et al, 2004). d-amphetamine sulfate was purchased under a Health Canada exemption from Sigma-Aldrich, UK (Dorset, England), caffeine was purchased from SigmaAldrich Canada (Oakville, ON, Canada), and ethyl alcohol was purchased from Fisher Scientific (Edmonton, AB, Canada).…”
Section: Pharmacological Challengesmentioning
confidence: 99%